The Analysis of the Implementation of Differentiated Instruction in Kindergarten - Alit Prapti Ratnadika, I Dewa Ayu (Jurnal Pendidikan dan Pembelajaran Bahasa Indonesia, 2012)
Abstract This thesis was conducted to analyze, and to describe the use of Differentiated Instruction (DI) in teaching and learning process in class B in Sukma Helen Flavel Kindergarten. This study analyzed two major aspects of DI namely the process of it (which was started from the learning preparation, DI?s implementation, and also assessment process); and also investigates the improvement of young learners writing skill after learning through DI. This thesis was designed as a descriptive study that adopted Miles and Huberman methodology in analyzing data. The subject of this thesis was the class B teacher and the students of class B and the object was the teaching process in class B which had implemented the DI. The data was collected through observation, documentation, and interview and analyzed by reducing the data, data display, and verification/conclusion drawing. The result showed that (1) by implementing the concept of Differentiated Instruction in teaching the young learners in class B, the teacher of class B was concerned to good preparation, such as preparing lesson plans that were ready to use, the various leaning material, the various learning sources, and learning media that are also ready to use in learning process. In term of its implementation, the teacher used various strategies and technique in class such as class trip, grouping, discussion, and drama. For evaluating the progress of the children, the teacher applied the systematic assessment procedure with the rich assessment instruments. The role of routines, classroom procedures, and also flexible grouping were really useful to help the children more discipline during learning. Furthermore, (2) the DI was able to improve the children?s early literacy especially in English. Keywords: Differentiated Instruction, Kindergarten